Alveolar soft-part sarcoma. Issue 12 (December 1982) - Hurt, R; Bates, M; Harrison, W
Abstract : Alveolar soft-part sarcoma is a slow-growing but nevertheless malignant soft tissue tumour arising in muscle. It occurs most frequently in young women and often presents as a painless swelling in an upper or lower limb. The swelling, which may have been present for a considerable time, is firm and appears to be well circumscribed but it may recur locally after excision. Blood-borne metastases to the lung are common and this is frequently the mode of presentation. Lymphatic metastases are unusual. The tumour is composed of nests of large cells and the histological appearances may resemble those of a renal adenocarcinoma (hypernephroma). Six new cases of this very rare tumour are presented and the published reports are reviewed.